A New Era for Management Accountants in Nigeria: A Guide to Achievement of Enhanced Organizational Performance and Success - Habib, Maryam Abdullah (International Journal For Research In Business, Management And Accounting, 2021)
Management accountants, in the conventional and contemporary age, have contributed to the development of organisations with regards organisational performance and success which has proven to be latent in Nigeria. The differences in development of organisational performance are dependent of the factors which have influenced both facets of roles of management accountants in Nigeria. This study compares the conventional and contemporary roles of management accountants and their contribution towards enhanced organisational performance and success in Nigeria. Secondary sources were analysed and information was gathered in the bid to produce literature on the issue of concern. The study shows that even with its current situation, management accountants, to varying extents, contribute to organisational performance and success. The study serves as a steer to academicians, potential employees, practicing management accountants and students in ensuring that these roles move with changes in the business environment for the sake of organisational performance and success.